Pola Komunikasi Konsensual Orang Tua dalam Membentuk Perilaku Tanggung Jawab Remaja Usia 17-18 Tahun di Perumahan Papan Bestari 2 Kota Pasuruan - Solichah, Desy Riamadhan; Lestari, Gunarti Dwi (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The purpose of this study is to analyze and describe parents' consensual communication patterns in shaping the responsible behavior of adolescents aged 17-18 years at Papan Bestari 2 Housing, Pasuruan City. This research uses descriptive qualitative method. The results of the study show that parents who apply consensual communication patterns are parents who are open to teenagers by getting used to telling stories, discussing, andsharing to adolescents, so that parents also provide intense supervision and attention to adolescents to be able to monitor their development. In forming responsibilities in adolescents, parents get used to planting from an early age to give concrete examples, give space and always provide supervision. The supporting factor is in the form of giving space to adolescents and the knowledge possessed by parents about the condition of adolescents, while the inhibiting factor is that adolescents are less able to regulate their emotions so they are less able to adjust the way of communication with older people.